2000
DOI: 10.1023/a:1002090627601
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A new assay was designed, named checker, that measures the individual response to light in the fruitfly Drosophila melanogaster larva. In this assay the Drosophila larva apparently modulates its pattern of locomotion when faced with a choice between a dark and lit environment by orienting its movement towards the dark environment. We show that, in this assay, a response to light can be measured as an increase in residence time in the dark versus the lit quadrant. Mutations that disrupt phototransduction in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Wild-type larvae express rhodopsins (Sprecher et al, 2007), which are classical G-protein coupled receptors. Consequently, in the absence of ChR2, wild-type larvae display an aversive response to light (Hassan et al, 2000). To eliminate the endogenous light response, we tested the effects of introducing the iav-GAL4 and UAS-ChR2 in a norpA P24 background, which disrupts a phospholipase C critical for the larval photoresponse (Hassan et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type larvae express rhodopsins (Sprecher et al, 2007), which are classical G-protein coupled receptors. Consequently, in the absence of ChR2, wild-type larvae display an aversive response to light (Hassan et al, 2000). To eliminate the endogenous light response, we tested the effects of introducing the iav-GAL4 and UAS-ChR2 in a norpA P24 background, which disrupts a phospholipase C critical for the larval photoresponse (Hassan et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…More than 35 years ago it was reported that Drosophila melanogaster larvae are photophilic in early stages, photoneutral in later stages, and photonegative in the end of the larval life (Manning and Markow, 1981; Markow, 1981). In contrast to this early description, a general consensus nowadays in most of the reports is that Drosophila larvae are photophobic during early stages of development (Godoy-Herrera et al, 1992; Sawin-McCormack et al, 1995; Busto et al, 1999; Warrick et al, 1999; Hassan et al, 2000; Mazzoni et al, 2005; Scantlebury et al, 2007; Gong, 2009; Keene et al, 2011; von Essen et al, 2011; Yamanaka et al, 2013). However, how phototaxis is altered or maintained during later stages remains debated.…”
Section: Introductionmentioning
confidence: 98%
“…Larval navigation is based on a combination of forward movements (called runs) and reorientations (called turns) (Luo et al, 2010; Gomez-Marin et al, 2011; Lahiri et al, 2011; Gershow et al, 2012; Kane et al, 2013). Changes in light-intensity elicit turning behavior (Busto et al, 1999; Hassan et al, 2000, 2005; Scantlebury et al, 2007; Kane et al, 2013). During these turns larvae move their head from one side to the other (called head-sweep) to probe the environment (Busto et al, 1999; Hassan et al, 2000, 2005; Scantlebury et al, 2007; Kane et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another assay, a larva crosses light/dark boundaries on a checkerboard test. In this case, the light/dark choice is encountered frequently [8, 12]. In one other assay, light is shed on crawling larvae and their responses to on/off switch of light are monitored and recorded [8, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%